Optimasi Aktivitas Bakteriosin yang Dihasilkan oleh Bakteri Lactobacillus plantarum dari Minuman Ce Hun Tiau - Sari, Rafika; Apridamayanti, Pratiwi; Octaviani, Melly (UI Scholars Hub, 2018)
Bacteriocin is a protein compound with a small molecular weight that has an antibacterial activity. Bacteriocin has been widely applied as a natural food preservative, as it effectively prevents the growth of pathogenic bacteria in foods and beverages. The aim of this research was to know the activity of bacteriocin produced by lactic acid bacteria Lactobacillus plantarum from Ce hun tiau beverages against Escherichia coli and Staphylococcus aureuswith different pH and temperature treatments. In this study, Lactobacillus plantarum bacteria isolated from Ce hun tiau beverages were characterized by Gram staining test. Bacteriocin was extracted from Lactobacillus plantarum bacteria which had been incubated in deMan Rogose Sharpe Broth media. Confirmation test using proteolytic enzyme and bacteriocin activity test with different pH (2, 4, 6, 8, and 10) and temperature (40°, 60°, 80°, 100°, and 121°C) treatments were conducted. The results showed that bacteriocin hadantibacterial activity against Escherichia coli but had no activity against Staphyloccus aureus. The inhibition zone was formed at pH 2 to 6 and at temperature range of 40°C to 121°C.